Plato’s Myth of the Digital Cave: The Role of Generative Artificial Intelligence in the World of Ideas and its Content as the Shadow of Art - Garrido-Merchán, Eduardo C. (Razón y fe, 2026)
This work explores two hypotheses regarding the role of artificial intelligence from a Platonic perspective. The first proposes that a utopian deep neural network —trained on an infinite amount of data encompassing all objective knowledge of the world— could have its place within Plato’s World of Ideas. These systems are already generating representations, such as chess strategies, that humans cannot comprehend. Therefore, it is suggested that machine learning models, thanks to their capacity to generate representations of the sensible world, can be considered an approximate shadow of Platonic Ideas, offering us a new way of thinking about the relationship between the visible and the intelligible. The second hypothesis, more practical and critical in nature, follows from the first. It warns of the risks posed by content generated by such artificial intelligences, especially when images and texts are created with negative intent. If art, for Plato, was already a copy of reality —a shadow in the Cave— then AI-generated content would be a “shadow of that shadow”: a Second Level of the Cave. In this scenario, we may find ourselves increasingly trapped in a Digital Cave, perceiving representations ever further from the truth, without realizing that we have stopped looking at reality itself.